2018
DOI: 10.3390/ma11060900
|View full text |Cite
|
Sign up to set email alerts
|

Waste-Based Pervious Concrete for Climate-Resilient Pavements

Abstract: For the sake of environmental protection and circular economy, cement reduction and cement substitutes have become popular research topics, and the application of green materials has become an important issue in the development of building materials. This study developed green pervious concrete using water-quenched blast-furnace slag (BFS) and co-fired fly ash (CFFA) to replace cement. The objectives of this study were to gauge the feasibility of using a non-cement binder in pervious concrete and identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…Results of compressive strength development were indicated that S and FA reacted with water and then with calcium hydroxide via a pozzolanic reaction to form hydration products (i.e., calcium silicate hydrate (C-S-H) and/or calcium aluminium silicate hydrate (C-A-S-H) colloids). These findings are consistent with those reported in previous studies [18,24] and it was produced produces viscous hardening behavior in the cementless composites [23].…”
Section: Flowabilitysupporting
confidence: 93%
See 1 more Smart Citation
“…Results of compressive strength development were indicated that S and FA reacted with water and then with calcium hydroxide via a pozzolanic reaction to form hydration products (i.e., calcium silicate hydrate (C-S-H) and/or calcium aluminium silicate hydrate (C-A-S-H) colloids). These findings are consistent with those reported in previous studies [18,24] and it was produced produces viscous hardening behavior in the cementless composites [23].…”
Section: Flowabilitysupporting
confidence: 93%
“…Samples were compared with standard Portland cement mortar in terms of mechanical properties, permeability and microstructure. The proposed material is intended to be used as a controlled low-strength material, pervious concrete, reinforced recycled concrete and for other engineering applications [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The speed of urbanization has reached an unprecedented level over the past few decades. During the progress of urbanization, impervious pavement materials, such as cement concrete and asphalt concrete, have expanded rapidly, and almost all city areas have been covered with these impermeable materials, thereby causing major and fatal urban flooding [1][2][3]. Multiple flood disasters have proven that conventional rainwater management approaches and existing flooding defense structures are ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of Chinese sponge city construction, PC will be widely applied in road structure [13]. Therefore, PC is of great significance for mitigating climate change, solving urban problems, and promoting the development of human society [14][15][16].The main properties of PC are strength, permeability, and durability. A porous structure is the key feature of PC, and porosity is the most important factor influencing mechanical strength, permeability, and durability.…”
mentioning
confidence: 99%
“…With the development of Chinese sponge city construction, PC will be widely applied in road structure [13]. Therefore, PC is of great significance for mitigating climate change, solving urban problems, and promoting the development of human society [14][15][16].…”
mentioning
confidence: 99%